Quercetin and polycystic ovary syndrome - Ma, Congshun; Xiang, Qianru; Song, Ge; Wang, Xuefei (Frontiers in Pharmacology, 2022)
Polycystic ovary syndrome (PCOS) is a reproductive endocrine disease, and results to opsomenorrhea or amenorrhea, hairy, acne, acanthosis, infertility, abortion. In the long term, PCOS may also increase the risk of endometrial cancer, diabetes, hypertension, dyslipidemia and other diseases. Till now there is no specific drug for PCOS due to the unclearness of the cause and pathogenesis, as current treatments for PCOS only target certain symptoms. Quercetin (QUR) is a flavonoid drug widely found in Chinese herbal medicines, fruits, leaves, vegetables, seeds and plants roots. Studies on other diseases have found that QUR has anti-oxidant, anti-inflammatory, anti-insulin resistance, anti-cancer and other effects. Some studies have shown that serum testosterone (T), luteinizing hormone (LH), the LH/follicule-stimulating hormone (FSH) ratio, fasting glucose, fasting insulin, HOMA-IR and lipid levels are reduced in PCOS patients with QUR treatment. However, the mechanisms of QUR in PCOS patients have not been completely elucidated. In this review, we retrospect the basic characteristics of QUR, and in vitro studies, animal experiments and clinical trials of QUR and plant extracts containing QUR in the treatment of PCOS. We also summarized the effects and mechanism of QUR in ovarian cells in vitro and PCOS model rats, the changes in relevant parameters after QUR administration in PCOS patients, and its potentially therapeutic applications.